3-O-Substituted-3′,4′,5′-trimethoxyflavonols: synthesis and cell-based evaluation as anti-prostate cancer agents - Li, Xiang (Bioorg Med Chem, 2017)
Twenty-two 3-O-substituted-3′,4′,5′-trimethoxyflavonols have been designed and synthesized for their anti-proliferative activity towards three human prostate cancer cell lines. Our results indicate that most of them are significantly more potent than the parent 3′,4′,5′-trimethoxyflavonol in inhibiting the cell proliferation in PC-3 and LNCaP prostate cancer cell models. 3-O-Substituted-3′,4′,5′-trimethoxyflavonols have generally higher potency towards PC-3 and LNCaP cell lines than the DU145 cell line. Incorporation of an ethyl group to 3-OH of 3′,4′,5′-trimethoxyflavonol leads to 3-O-ethyl-3′,4′,5′-trimethoxyflavonol as the optimal derivative with up to 36-fold enhanced potency as compared with the corresponding lead compound 3′,4′,5′-trimethoxyflavonol, but with reversed PC-3 cell apoptotic response. Introduction of a dipentylaminopropyl group to 3-OH increases not only the antiproliferative potency but also the ability in activating PC-3 cell apoptosis. Our findings imply that modification on 3-OH of trimethoxyflavonol can further enhance its in vitro anti-proliferative potency and PC-3 cell apoptosis induction.